Literature Review: Analysis of Creativity and Innovation in Entrepreneurship - Asiyah; Rusnandari Retno Cahyani (Kawakib: Journal of Multidisciplinary Research, 2025)
Creativity and innovation are the main foundations of the dynamic world of entrepreneurship. This article aims to analyze the crucial role of creativity and innovation in shaping entrepreneurial characteristics and the factors that influence them. The method used is a literature review, referencing various current literature sources. The analysis shows that entrepreneurship is not merely an economic activity, but rather a manifestation of creative ability to identify opportunities and innovatively create added value. Entrepreneurial characteristics are significantly influenced by family environment, education, and work experience. Furthermore, individual creativity is triggered by external factors such as environmental stimulation, resources, and democratic parenting styles. In conclusion, entrepreneurial success depends on the integration of a visionary mindset and the ability to implement new ideas to satisfy customers amidst market competition.